An User-Driven Active Way to Push ACL in Software-Defined Networking - Yu, Haisheng; Liu, Dong; Wang, Wenyong; Li, Keqiu; Zou, Sai; Liu, Zhaobin; Liu, Yan (Parallel and Distributed Computing, Applications and Technologies, 2022)
Compared with the traditional network, Software-Defined Networking (SDN) provides a more convenient network paradigm to build Access Control List (ACL) application. There has been a few studies focusing on ACL application in SDN up to now, but most of the existing work adopts a reactive way to enforce ACL, resulting in new ACL update can not take effect immediately. In this paper, we propose CLACK, an approach for user-driven centralized ACL in SDN. We implement CLACK on both Floodlight and ONOS controller. The experimental results show that CLACK has a better performance than the existing Floodlight firewall application.